Підвищення ефективності механізмів управління закладами сфери охорони здоров’я - Яремко, І. І.; Yaremko, I. I. (Видавництво Львівської політехніки, 2021)
Узагальнено теоретичні засади державних та внутрішньогосподарських механізмів управління закладами сфери охорони здоров’я, проаналізовано наявні теоретико-методологічні засади їх побудови та практичну дієвість у сучасних умовах. Наведено деякі приклади зарубіжної практики й оцінено пропоновані в дослідницьких працях українських науковців пропозиції щодо системних змін управлінських технологій та можливості їхнього впровадження медичними закладами. Досліджено базові засади аналітичної оцінки ефективності функціонування механізмів та їхню дієвість в управлінні закладами галузі. Сформульовано шляхи оптимізації механізмів в управлінській системі закладів охорони здоров’я та підходи до аналітичної оцінки ефективності їх використання.

The article summarizes the theoretical foundations of public and domestic management mechanisms in the field of health care. The essence, structure and functional orientation of mechanisms in the theory of management and the specifics of their formation for health care institutions are revealed. The analysis of the level of validity of the existing theoretical and methodological bases of construction of mechanisms in the system of national and internal economic management in the medical field, their practical efficiency and effectiveness in modern Ukrainian conditions is carried out. The content and functional orientation of the system changes of management technologies and ways of increase of efficiency of mechanisms in management of establishments of branch offered in research works are estimated. Some examples of foreign practice in the field of health care organization are given with an assessment of the possibilities of implementing certain components of foreign experience in Ukrainian practice. Based on the results of the assessment of theoretical and analytical principles and information on the practice of domestic health care institutions, some proposals are formulated to improve the conceptual principles of management of domestic health care institutions, ways to optimize mechanisms in the management system and approaches to analytical evaluation of their functioning. The results that have the greatest practical significance include the proposed approaches and ways to develop qualified management in medical institutions in the industry through the introduction of modern economic mechanisms in management systems. Among them, it is proposed to implement in the existing management systems of health care facilities a system of market tools adequate to the industry specifics, including business planning, the latest mechanisms and tools of financial and strategic management. The development of public-private partnership in the medical field is considered.
Improving the efficiency of management mechanisms of health care institutions
Keywords: сфера охорони здоров’я; медичний заклад; управління; механізми; ефективність; концепція; sphere of health care; medical institution; management; mechanisms; efficiency; concept